World experience of the electric power industry restructuring - Shabalina, L.; Bulavka, E. (Економічний вісник Донбасу, 2017)
The article reveals the factors affecting the electricity consumption in the world. Based on the study of the world experience in the restructuring of the electric power industry, five groups of methods are identified to improve its efficiency: organizational, consolidation of markets, financial, tax and environmental. У статті виявлено фактори, що впливають на споживання електроенергії в світі. На основі вивчення світової досвіду реструктуризації електроенергетичної галузі виділено п'ять груп методів щодо підвищення її ефективності: організаційний, консолідації ринків, фінансовий, податковий та екологічний. В статье выявлены факторы, влияющие на потребление электроэнергии в мире. На основе мирового опыта реструктуризации электроэнергетической отрасли выделены пять групп методов повышения ее эффективности: организационный, консолидации рынков, финансовый, налоговый и экологический.